PENGARUH KANDUNGAN INFORMASI ARUS KAS DARI AKTIVITAS INVESTASI, AKTIVITAS PENDANAAN DAN LABA KOTOR TERHADAP RETURN SAHAM - ., Subekti (PERMANA, 2010)
The purpose of this study was to determine the influence of Investment Cash Flow, Cash Flow and Gross Profit Funding of return is done on the company saham.Penelitian Miscellaneous Manufacturing Industry in Indonesia Stock Exchange. Data collection methods conducted in this study is the observation method of secondary data. The population in this study amounted to 25 Miscellaneous Manufacturing Industries companies based on financial reports and data Indonesian Capital Market Directory (ICMD) that exist on the Stock Exchange with the observation period 2007-2009. While the sampling of 15 companies Miscellaneous Manufacturing Industir using purposive sampling method. Phase analysis in this study include the classic assumption test, test multiple linear regression and hypothesis testing using SPSS software version 19. Based on the results of testing using the F test significant values ??of 3 variables is 0.046. If a significant value <.05 then the hypothesis is rejected (significant regression coefficient) this suggests that simultaneous Investing Cash Flow, Cash Flow Gross profit funding and has a significant influence on the Return Shares arrives. Furthermore, based on t test showed that only partially Gross Profit are having a significant influence on stock return because of significant value <0.05 while the Investment and Cash Flow Financing Cash Flow does not have a significant influence on Return of Shares made by the company because of its significance value> 0.05. Expected to further research to consider other factors in its effect on stock returns and the period of observation to maximum results. Key words: Investment Cash Flow, Cash Flow Financing, Gross Profit, Return Shares.